Tempat Potensial Perkembangbiakan (Maya Indeks) Nyamuk Aedes Sp. di Daerah Endemis Demam Berdarah Dengue (DBD) di Kabupaten Katingan - Amarullah, Novi; Raharjo, Mursid; Sutiningsih, Dwi (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background : Katingan Regency has experienced an increase in dengue fever cases in Central Kalimantan Province over the past three years, from 2020 to 2023, with an incidence rate in 2023 of 168.4 per 100,000 population and a Case Fatality Rate (CFR) of 0.66%. This is due to the Maya Index, which is a potential breeding ground for Aedes sp mosquitoes, remaining a problem. Therefore, research will be conducted to detect the Maya Index of Aedes sp mosquitoes in dengue fever endemic areas in Katingan Regency.Methods : This study was conducted using an observational research method with a cross-sectional approach in April 2024. The population in this study consisted of all cases of dengue fever in January–February 2024, with a sample size of 113 samples. The sampling technique used was random sampling. Data were obtained through direct observation and observation of the home environment using the visual larval method.Result : The Breeding Risk Index (BRI) was in the moderate category, with 52 (46%) homes, while the Hygiene Risk Index (HRI) was also in the moderate category, with 55 (48.7%) homes. in dengue endemic areas, it is in the moderate category (BRI 2/HRI 2), which is 27 (23.9%) houses. Most houses in dengue endemic areas in Katingan Regency are in the high Maya Index status, which is 51 (45.1%) houses.Conclusion : Houses with low to moderate BRI will have less potential for having positive larval containers than houses with high BRI. Houses with low to moderate HRI have higher positive larval containers than houses with high HRI.